How well do clinical pain assessment tools reflect pain in infants? - Rebeccah Slater; Anne Cantarella; Linda Franck; Judith Meek; Maria Fitzgerald (PLoS Medicine)
Background Pain in infancy is poorly understood, and medical staff often have difficulty assessing whether an infant is in pain. Current pain assessment tools rely on behavioural and physiological measures, such as change in facial expression, which may not accurately reflect pain experience. Our ability to measure cortical pain responses in young infants gives us the first opportunity to evaluate pain assessment tools with respect to the sensory input and establish whether the resultant pain scores reflect cortical pain processing. Methods and findings Cortical haemodynamic activity was measured in infants, aged 25-43 wk postmenstrual, using near-infrared spectroscopy following a clinically required heel lance and compared to the magnitude of the premature infant pain profile (PIPP) score in the same infant to the same stimulus (n = 12, 33 test occasions). Overall, there was good correlation between the PIPP score and the level of cortical activity (regression coefficient = 0.72, 95% confidence interval [CI] limits 0.32-1.11, p = 0.001; correlation coefficient = 0.57). Of the different PIPP components, facial expression correlated best with cortical activity (regression coefficient = 1.26, 95% CI limits 0.84-1.67, p < 0.0001; correlation coefficient = 0.74) (n = 12, 33 test occasions). Cortical pain responses were still recorded in some infants who did not display a change in facial expression. Conclusions While painful stimulation generally evokes parallel cortical and behavioural responses in infants, pain may be processed at the cortical level without producing detectable behavioural changes. As a result, an infant with a low pain score based on behavioural assessment tools alone may not be pain free.